Pemberdayaan Masyarakat Berbasis Nilai-Nilai Adat Istiadat Sunda - Ritonga, Anas Habibi; Kurniawan, Hariri; Yandi, Ali (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2021)
We can find community empowerment based on traditional values in the indigenous people of Kampung Cirendeu. The indigenous people of Kampung Cireundeu are able to empower the community through traditional values. Community empowerment is basically a process that is carried out towards a state from inability to being able from helplessness to being empowered. The purpose of this study is to analyze and find out how the implementation of community empowerment and the process of the indigenous people of Kampung Cireundeu building a system of traditional values. This study uses a qualitative method with an ethnographic approach. The results of this study found the facts that: First, the traditional values found in the traditional community of Kampung Cirendeu are the source of the creation of a food self-sufficiency system. Second, the very simple process carried out by the indigenous people of Kampung Cireundeu in building a system of traditional values through the concepts of pamali, nirukeun, and ngabisakeun. Third, based on the results of the researcher's analysis of the implementation of the empowerment of the indigenous people of Kampung Cireundeu, it was carried out through the first, Bina Jalmi. Second and Business Development.